Explosive vapour/particles detection using SERS substrates and a hand-held Raman detector. Issue 42 (28th July 2021) - Heleg-Shabtai, Vered; Zaltsman, Amalia; Sharon, Mali; Sharabi, Hagai; Nir, Ido; Marder, Dana; Cohen, Guy; Ron, Izhar; Pevzner, Alexander
Abstract : We developed and optimized surface-enhanced Raman spectrometry (SERS) methods for trace analysis of explosive vapour and particles using a hand-held Raman spectrometer in the field. Abstract : We developed and optimized surface-enhanced Raman spectrometry (SERS) methods for trace analysis of explosive vapour and particles using a hand-held Raman spectrometer in the field. At first, limits of detection (LODs) using SERS methods based on a colloidal suspension of gold nanoparticles were measured under alkaline conditions and are as follows: pentaerythritol tetranitrate (PETN) (1.5 × 10 −6 M, 6.9 ng), 1, 3, 5, 7-tetranitro-1, 3, 5, 7-tetrazoctane (HMX), 8.1 × 10 −6 M, 35 ng; urea nitrate (UN), 9.2 × 10 −4 M, 165 ng; 2, 4, 6-trinitrotoluene (TNT), 1.1 × 10 −7 M, 0.35 ng. We developed SERS substrates that demonstrate the wide applicability of this technique for use in the field for explosive vapour and particles adsorbed on a surface based on Au nanoparticles that were optimal for the detection of the target materials in solution. Au nanoparticles were modified onto quartz fibres or a polyurethane sponge for vapour/particles detection. SERS detection of vapours of 2, 4-dinitrotoluene (2, 4-DNT) and 1, 3-dinitrobenzene (1, 3-DNB) was shown by sampling vapours onto Au-modified quartz fibres followed by hand-held Raman analysis with estimated minimum detection levels of 3.6 ng and 54 ng, respectively. The detection of 2, 4-DNT using sponge-based SERS decorated with Au nanoparticles was also demonstrated; however, the sensitivity was lower than that observed using quartz fibres. The detection of TNT on a surface was performed by utilizing quartz-fibres precoated with alumina and modified with Au nanoparticles, and the detection of 10 μg (0.53 μg cm −2 ) of TNT was demonstrated.